Therapeutic drug monitoring of mitotane: Analytical assay and patient follow‐up. (21st May 2017) - Feliu, Catherine; Cazaubon, Yoann; Guillemin, Helene; Vautier, Damien; Oget, Olivier; Millart, Hervé; Gozalo, Claire; Djerada, Zoubir
Abstract: Adrenocortical carcinoma (ACC) is an aggressive malignancy of the adrenal gland. Mitotane ( o, p' ‐DDD) is the most effective chemotherapy for ACC. According to the literature, mitotane plasma trough concentrations within 14–20 mg L −1 are correlated with a higher response rate with acceptable toxicity. Therapeutic drug monitoring (TDM) of mitotane is therefore recommended. The aim of this study was to propose a robust and simple method for mitotane quantification in plasma. The validation procedures were based on international guidelines. Sample preparation consisted of a single protein precipitation with methanol using 100 μL of plasma. The supernatant was submitted to liquid chromatography coupled with ultra‐violet detection at 230 nm. Mitotane retention time was 7.1 min. The limit of detection was 0.1 mg L −1 and the limit of quantification was 0.78 mg L −1 . The assay demonstrated a linear range of 0.78–25 mg L −1 with correlation coefficients ( r 2 ) at 0.999. Inter‐ and intra‐assay precision was <4.85%. Evaluation of accuracy showed a deviation <13.69% from target concentration at each quality control level. This method proved easy and rapid to perform mitotane TDM and required a small volume of sample. It was successfully applied to routine TDM in our laboratory.